2012
DOI: 10.1038/nature11174
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Plasmodium falciparum diversity in natural infections by deep sequencing

Abstract: Malaria elimination strategies require surveillance of the parasite population for genetic changes that demand a public health response, such as new forms of drug resistance. 1,2 Here we describe methods for large-scale analysis of genetic variation in Plasmodium falciparum by deep sequencing of parasite DNA obtained from the blood of patients with malaria, either directly or after short term culture. Analysis of 86,158 exonic SNPs that passed genotyping quality control in 227 samples from Africa, Asia and Oce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
617
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 479 publications
(675 citation statements)
references
References 41 publications
38
617
0
Order By: Relevance
“…4). An additional 354 sequences of cosmopolitan P. falciparum strains from the Sanger Institute supported this conclusion (34), indicating that all human P. falciparum sequences coalesced to a single common ancestor. Thus, the addition of over 1,000 new P. falciparum sequences, including over 600 from individuals living near wild-ape populations, confirmed that P. falciparum is of gorilla origin and emerged in humans following a single cross-species transmission event (4).…”
Section: Discussionmentioning
confidence: 52%
“…4). An additional 354 sequences of cosmopolitan P. falciparum strains from the Sanger Institute supported this conclusion (34), indicating that all human P. falciparum sequences coalesced to a single common ancestor. Thus, the addition of over 1,000 new P. falciparum sequences, including over 600 from individuals living near wild-ape populations, confirmed that P. falciparum is of gorilla origin and emerged in humans following a single cross-species transmission event (4).…”
Section: Discussionmentioning
confidence: 52%
“…No significant SNPs showed r 2 > 0.5 with any adjacent SNPs with MAF >0.05. Whole-genome sequencing of 227 P. falciparum field isolates indicated that r 2 fell below 0.10 within 1 kb in all parasite populations studied (18). The markers in our GWAS were, on average, 7 kb apart, so it may be that other loci associated with parasite clearance were not detected because they were not in LD with a genotyped SNP.…”
Section: Discussionmentioning
confidence: 98%
“…To test whether infections were monoclonal or polyclonal, we used the F WS statistic (86,87). To enable direct F WS comparisons between P. falciparum and P. vivax isolates, which had different numbers of loci, we bootstrapped each calculation 1,000 times, randomly selecting 5,000 variable sites for each isolate and each replicate.…”
Section: Discussionmentioning
confidence: 99%